N-acetylglucosaminyltransferase V inhibits the invasion of trophoblast cells by attenuating MMP2/9 activity in early human pregnancy. Issue 11 (November 2015) - Deng, Qinyin; Chen, Ying; Yin, Nanlin; Shan, Nan; Luo, Xin; Tong, Chao; Zhang, Hua; Baker, Philip N.; Liu, Xiru; Qi, Hongbo
Abstract: Introduction: The invasion and migration of trophoblast cells are essential steps of normal placentation and successful pregnancy. The process is well-regulated by many factors at the fetal–maternal surface. Inadequate invasion by trophoblast cells may lead to poor perfusion of the placenta or complications such as preeclampsia (PE). Accumulating evidence suggests that N-acetylglucosaminyltransferase V (MGAT5) is correlated with tumor invasion and metastasis. Our objective was to characterize MGAT5 expression and function during placental development. Methods: The expression of MGAT5 in humans in placental tissue from the first trimester was determined by immunohistochemistry. To investigate whether MGAT5 regulates trophoblast invasion and migration, we investigated invasion/migration of the HTR8/SVneo trophoblast cells and used human villous explants. Cell proliferation and apoptosis were measured by CCK-8 assay and flow cytometry, respectively. The activity of matrix metalloproteinase (MMP) 2/9, and the expression of tissue inhibitors of metalloproteinases (TIMPs) 1/2 were determined by gelatin zymography and Western blot, respectively. Results: MGAT5 was specifically localized within the cytotrophoblast, the syncytiotrophoblast and the trophoblast columns of human placental villi, decidual cells and some extravillous cells in the maternal decidua. MGAT5 shRNA significantly enhanced the invasion and migration capability of HTR8/SVneo cells, and increased villous explant outgrowth but did not affect proliferation and apoptosis of the trophoblast. The enhanced effect of MGAT5 shRNA on trophoblast cell invasion was associated with increased gelatinolytic activity of MMP2/9 and decreased expression of TIMP1/2. Discussion and conclusion: Our data support a role for MGAT5 in the inhibition of human trophoblast cell invasion and migration during early pregnancy by direct or indirect regulation of MMP2/9 activity. Highlights: MGAT5 was expressed in trophoblast. MGAT5 inhibits human trophoblast migration and invasion. Genetically knockdown of MGAT5 improve trophoblast migration and invasion by regulating activity of MMP2/9.